2017
DOI: 10.14309/crj.2017.20
|View full text |Cite
|
Sign up to set email alerts
|

Novel Use of a Uniquely Designed, Lumen-Apposing, Metal Stent in Benign Gastric Outlet Obstruction in Two Patients

Abstract: Current guidelines recommend management of benign gastric outlet obstruction (GOO) with serial dilations. Self-expanding metal stents are effective, but their use is complicated by high rates of migration. We present two cases from our institution where a uniquely designed, lumen-apposing metal stent (LAMS) was successfully used to alleviate benign GOO without stent migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Diagnosis is usually made with imaging and confirmed via endoscopy. A total of 138 patients were reviewed in the 4 retrospective studies and 13 case reports [13][14][15][16][17][18][19][20][21][22][23][24]. The patients were predominantly female, with ages ranging from 18-86 years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Diagnosis is usually made with imaging and confirmed via endoscopy. A total of 138 patients were reviewed in the 4 retrospective studies and 13 case reports [13][14][15][16][17][18][19][20][21][22][23][24]. The patients were predominantly female, with ages ranging from 18-86 years.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 20 patients in the reviewed literature had a LAMS placed to treat a gastric stricture [14][15][16][17][18][19][20]. The etiology of the strictures included anastomotic strictures, caustic injury, peptic ulcer disease with resultant peptic stricture formation, pyloric stenosis and 1 case of malignant pyloric stenosis (Fig.…”
Section: Gastric Stricturesmentioning
confidence: 99%
See 2 more Smart Citations
“…I N TOTAL, 19 studies and case reports were identified and included in the review [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] (Table 1 and Fig. S1).…”
Section: Literature Reviewmentioning
confidence: 99%